Dimensional construction and morphological tuning of heterogeneous MoS2/NiS electrocatalysts for efficient overall water splitting. Issue 21 (16th May 2018) - Zhai, ZhangJie; Li, Chao; Zhang, Lei; Wu, Han-Chun; Zhang, Lei; Tang, Ning; Wang, Wei; Gong, Jinlong
Abstract : Heterogeneous MoS2 /NiS is dimensionally constructed and selectively fine tuned to achieve different morphologies with multi-level interfaces. Abstract : Water splitting for hydrogen production urges the development of cheap, efficient, and durable electrocatalysts. This paper describes the dimensional construction of nickel sulfide (NiS) and molybdenum disulfide (MoS2 ) with heterogeneous structures for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). The morphologies of MoS2 /NiS can be finely tuned to aggregations, nanowires and nanocuboids by controlled addition of dioctyl sodium sulfosuccinate (AOT) and hexadecyl trimethyl ammonium bromide (CTAB) as surfactants. MoS2 /NiS nanosheet coupled nanocuboids (MoS2 /NiS NCs) exhibit the best and most stable electrocatalytic activity with 92 and 271 mV overpotentials at 10 and 15 mA cm −2 for the HER and the OER. MoS2 /NiS NCs as an electrolyzer in alkaline media at a current density of 10 mA cm −2 can deliver a cell voltage of 1.61 V with remarkable 45 h durability, making them an ideal catalyst towards practical application for water splitting.